Hijab, Cadar dan Kesalehan Perempuan dalam Konteks Kontemporer: Interpretasi Perspektif Ali al-Shabuni dalam QS. al-Nur Ayat 30–31 - Ahmad Bastari (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This article aims to examine Ali al-Shabuni views on the hijab and veil in QS. al-Nur [24]: 30-31. The results of al-Shabuni interpretation in the book Rawai' al-Bayan will be analyzed by the author to make them relevant in the current context. By using a qualitative-descriptive method, this article concludes that according to Ali al-Shabuni, the hijab and veil are obligatory based on the interpretation of QS. al-Nur [24]: 30-31. This refers to the current condition where many women actually open their genitals with the aim of being shown in the public sphere which has the potential to cause slander. While the scholars forbid opening the face, if it has the potential to cause slander and can foster lust for other men who are not mahram. Therefore, the use of the hijab and veil is very relevant in the contemporary context, even though there are many pros and cons that arise in society, because wearing the veil can have a positive impact on the women who wear it. Apart from that, the stigma attached to the veil which is synonymous with 'terrorists' does not affect this mandatory law, because in fact they are just rogues. The fact is that some are veiled but they are not terrorists. This article contributes to providing new insights that can serve as an ethical-theological basis for strengthening the identity of Muslim women in the modern era, and opens up space for understanding interpretations in the context of today's social reality.